PERANAN TENTARA KEAMANAN RAKYAT TEMANGGUNG DALAM PERJUANGAN MEMPERTAHANKAN KEMERDEKAAN TAHUN 1945-1946 - Fikriyah, Sofa (Candi, 2015)
In early of independence, the political of Temanggung was began by establishment of KNID Temanggung, KNID?s members represent a diverse group of particular political parties. Influential political party in Temanggung is Masyumi, PNI and PKI, but the competition has not seen because Temanggung?s community is more focused on the struggle for independence. In term of national defense, in early of establishment Indoesian, the government has not dared to form a national army, thus formed BKR (Badan Keamanan Rakyat) which purpose to maintaining the public safety and public security under BPKKP (Badan Penolong Keluarga Korban Perang). In Temanggung, BKR formed in mid September with a half-strength plaaton. When the Allies forces came to Indonesia, BKR considered ineffective, so on 5th October 1945 the government issued a declare about changes BKR to TKR (Tentara Keamanan Rakyat). With that declare, Bambang Soegeng as commander BKR Temanggung opened registration for TKR Temanggung members in government offices and in headquarters of TKR Temanggung. At the Japan disarmament effort, TKR Temanggung prefers diplomacy over confrontation. TKR Temanggung treated Japanese prisoners as a old brothers. At Palagan Ambarawa war, TKR Temanggung send Battalion I/Res.18 troops under command of Major Soejoto to front Ambarawa. On 29th November 1945, Soejoto troops met Allied forces convoy and battles in Ngipik village. Seojoto and 20 troops killed in that battled.